Can we evidence-base injury prevention and management in women`s football? A scoping review - Okholm Kryger, K.; Wang, A.; Mehta, R.; Impellizzeri, F. M.; Massey, A.; Harrison, M.; Glendinning, R.; McCall, A. (Research in Sports Medicine, 2023)
This review aimed, as part of a larger FIFA project aiming to steer women`s football research, to scope literature on any level of competitive football for women, to understand the current quantity of research on women`s football injuries. The study reviewed all injury-related papers scoped by a recent scoping review mapping all published women's football research with an updated search performed on 23 February 2021. Eligibility criteria assessment followed the recent scoping review with injury-specific research focus. A total of 497 studies were scoped. Most studies contained an epidemiological (N = 226; 45%) or risk factors assessment (N = 105; 21%). Less assessed areas included financial burden (N = 1; <1%) and injury awareness (N = 5; 1%). 159 studies (32%) assessed injuries of the whole body. The most common single location assessed in the literature was the knee (N = 134, 27%), followed by head/face (N =108, 22%). These numbers were, however, substantially lowered, when subdivided by playing level and age-group. The volume of research focuses especially on descriptive research and specific body locations (head/face and knee). Although information can be taken from studies in other sports, more football-specific studies to support management and prevention of injuries are warranted.